URBANISATION ET CONTREURBANISATION DANS L’EUROPE D’APRÈS-GUERRE - IONEL MUNTELE (Revue Roumaine de Géographie)
This study is a result of the personal reflections about the one extremely intricate process, in a period with thorough change-overs: the urbanization. In a certain situation, to detect with mostly obviousness some trends, the study period has been extended at theentire XXth century. The most important purposes of this analysis, presented at the „Academic Days of Iaşi” (Sept. 2008) has been the followings: the constitution of one database about the dynamics of the urbanization in modern and contemporary Europe; the analysis of the measure were the classical models of the urban dynamics study (rank-size rule, the model of the central places) may be adapted of the recently complicated evolution derived from the change-over of the spatial reports between the urban system components, at everyscale; the obviousness of the various types of the urbanization, including the perspective of the engendered effects:urban displaying, urban congestion, periurbanization etc.